Peran Guru Dalam Mengoptimalkan Kurikulum Merdeka - Enjelita Putri; Fauziyah, Fauziyah; Merika setiawati; Hendri budi utama (CV.ITTC INDONESIA, 2025)
This article discusses the Merdeka Curriculum as a new educational policy in Indonesia aimed at providing flexibility in the learning process. This curriculum is driven by the need for an adaptive education system that responds to changing times and the challenges posed by the Covid-19 pandemic. The purpose of this study is to describe the definition, foundation, teacher roles, challenges, and implementation of the Merdeka Curriculum in schools. The method used is a literature study with a qualitative descriptive approach. The findings indicate that the Merdeka Curriculum offers an optimal space for the development of students' potential but still faces challenges in practical implementation. The results show that curriculum development plays a crucial role in educational institutions, and teachers must have the ability to deliver instruction effectively to realize the curriculum. Based on the analysis and conclusions, the author suggests that teachers should be able to keep up with technological advances, implement a curriculum that is constantly evolving, and prioritize tasks that need immediate completion.